Analysis of Errors in Solving Story Questions on Algebraic Operations Based Kastolan Theory Students SMP Negeri 6 Palu - Fitriyaningsih, Ari; Sugita, Gandung; Anggraini, Anggraini; Murdiana, I Nyoman (Universitas Ma'arif Lampung, 2024)
This research examines students' mistakes in solving mathematics story problems, especially algebraic arithmetic operation story problems, based on Kastolan theory and examines what factors cause students to make these mistakes. The type of research used in this research is descriptive qualitative. The place where the research was carried out was SMP Negeri 6 Palu. The subjects taken in this research were class VII students at SMP Negeri 6 Palu, consisting of 1 student with several considerations obtained as students with low MH abilities. Before analyzing the data obtained, it is validated first using member check. The data analysis techniques used in this research are data reduction, data presentation and drawing conclusions. The results of this research show that subject MH made 3 types of errors based on Kastolan's theory, namely: Conceptual Errors in the form of the subject not being able to apply the formula, classifying the form of variables in solving the problem when using the formula that has been obtained, the subject not writing completely the information known in the problem and errors in substituting known information into the question. Procedural errors in the form of irregularity in the solution steps used by the subject, there are several steps that are skipped so that the solution becomes wrong until the final stage of solving the problem. Technical error in the form of Subject MH making an error in calculating the value in the arithmetic operation shown in the subject only dividing by 2 each solution to get the result of the question in the problem because the subject did not understand the formula to be used and was not correct in substituting the value in the problem into problem solving. The factors that cause errors made by students are divided into two, namely internal and external factors. Internal factors include low basic knowledge regarding the form of arithmetic operations, solving steps for story questions and low knowledge of algebraic material. Lack of practice working on questions in the form of story problems and students' lack of accuracy in solving story problems. The external factor is that students are in a hurry when completing story problems because they want to finish them immediately and go to do other activities with their friends.